2023
DOI: 10.1021/acssuschemeng.3c03467
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose as Convenient Reaction Media for the FeCl3 Mediated Mechanochemical Synthesis of 3-Acylchromones

Satenik Mkrtchyan,
Vishal B. Purohit,
Viktor O. Iaroshenko

Abstract: A solvent free strategy for the mechanochemical synthesis of 3-acylchromones has been developed via FeCl3-nanocellulose mediated dehydrative coupling of ortho-hydroxyarylenaminones and carboxylic acids. The ortho-hydroxyarylenaminones undergo electrophilic domino cyclization followed by an unusual acylation event with carboxylic acids in the presence of FeCl3 as the catalyst and nanocellulose as the reaction media. The protocol was found to be simple, efficient, and environmentally benign to obtain a diverse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In the current paper, we present a new methodology that enables the efficient installation of the CF 3 functionality onto aromatic substrates through ipso -substitution of the NH 2 group using a commercially available pyrylium tetrafluoroborate reagent (Pyry-BF 4 ) and utilization of nanocellulose as the reaction medium. Furthermore, in our recent studies we noticed that nanocellulose can act as the best reaction medium for various mechanochemical transformations including reductive amidation of nitro compounds and for the synthesis of 3-acylchromones via dehydrative cross-coupling between ortho -hydroxyarylenaminones and carboxylic acids …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current paper, we present a new methodology that enables the efficient installation of the CF 3 functionality onto aromatic substrates through ipso -substitution of the NH 2 group using a commercially available pyrylium tetrafluoroborate reagent (Pyry-BF 4 ) and utilization of nanocellulose as the reaction medium. Furthermore, in our recent studies we noticed that nanocellulose can act as the best reaction medium for various mechanochemical transformations including reductive amidation of nitro compounds and for the synthesis of 3-acylchromones via dehydrative cross-coupling between ortho -hydroxyarylenaminones and carboxylic acids …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nanocellulose has received significant attention in mechanochemical transformations due to its unique physical and chemical properties. , Apart from having substantial biodegradability, nanocellulose possesses a high specific surface area, high crystallinity, high mechanical strength, and controllable reactive surface . The specific morphology including large surface area makes nanocellulose so effective as a solid reaction medium under the ball milling conditions. ,, Due the fully controllable reactivity, nanocellulose has also shown potential to be used as an additive, catalyst, or catalyst support in many organic transformations. , …”
Section: Introductionmentioning
confidence: 99%
“…Our starting point was the identification of appropriate reaction parameters for the synthetic protocols proposed here. Inspired from our recently developed approach on FeCl 3 nanocellulose-mediated mechanochemical of synthesis of 3acylchromones via dehydrative coupling of ortho-hydroxyarylenaminones and carboxylic acids 40 and continuing this research, we embarked to screen the similar conditions for other synthetic scenarios, particularly for amide bond formation. Deliberately, two sets of model reactions have been designed for the convenient synthesis of N-aryl/alkyl amide: (i) acylation of amines with carboxylic acids and (ii) reductive amidation of nitro compounds with carboxylic acids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Very recently, we have developed a solvent-free strategy for the mechanochemical synthesis of 3-acylchromones FeCl 3 nanocellulose-mediated dehydrative coupling of ortho-hydroxyarylenaminones and carboxylic acids. 40 The optimization studies of this acylation approach revealed that the utilization of 50 mol % of FeCl 3 as a catalyst with nanocellulose as reaction media and canola oil as lubricant led to the formation of 3-acylchromones with excellent yields. Then, on top of that, we decided to screen the similar conditions for other synthetic scenarios, particularly for the amide bond formation via reductive amidation of nitro compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…o -Hydroxyphenylenaminones ( o -HPEs) as structurally unique enaminones, have recently been well explored to rapidly access the privileged chromone skeleton through the cascade vinyl C–H bond functionalization/intramolecular chromone annulation process . In the past decade, the vast majority of uses for this synthetic strategy have constructed 3-substituted chromones through a wide variety of α-C­(sp 2 )–H bond functionalization, including alkylation, alkenylation, alkynylation, arylation, halogenation, acylation, acyloxylation, sulfenylation, selenylation, trifluoromethylation, etc. (Scheme a).…”
mentioning
confidence: 99%